Influence of nanocatalyst size on hydrogen formation during water radiolysis under ionizing radiation at room temperature - Mahmudov, H.M.; Ismayilova, M.K.; Hasanova, S.A.; Aliyev, S.M.; Akberov, O.E.; Azizova, K.V.; Jafarova, N.A. (Вопросы атомной науки и техники, 2016)
Formation of molecular hydrogen during radiolysis of water with Al²O³ nanoparticles of various sizes is
investigated. It was found that the molecular hydrogen yield depends on size of the catalyst. The yield of molecular
hydrogen formed on the surface of small nanoparticles is 1.4-1.6 times higher than that on the surface of large
nanoparticles. Homogeneuos distribution of nanocatalyst in the water and increase of the catalyst surface that is
adsorbing water molecules make the radiolysis more efficient. Досліджено утворення молекулярного водню при радіолізі води в присутності наночастинок Al²O³
різного розміру. Встановлено, що вихід молекулярного водню залежить від розміру частинок каталізатора.
Вихід молекулярного водню на поверхні наночастинок каталізатора малих розмірів у 1,4-1,6 разів більше, в
порівнянні з виходом на поверхні наночастинок більшого розміру. Підвищенню ефективності радіолізу
сприяють однорідний розподіл наночастинок каталізатора у водному середовищі і збільшення сумарної
поверхні каталізатора, на якій адсорбуються молекули води. Исследовано образование молекулярного водорода при радиолизе воды в присутствии наночастиц Al²O³
различного размера. Установлено, что выход молекулярного водорода зависит от размера частиц
катализатора. Выход молекулярного водорода на поверхности наночастиц катализатора малых размеров в
1,4-1,6 раз больше, по сравнению с выходом на поверхности наночастиц большего размера. Повышению
эффективности радиолиза способствуют однородное распределение наночастиц катализатора в водной
среде и увеличение суммарной поверхности катализатора, на которой адсорбируются молекулы воды.